2013
DOI: 10.1597/11-125
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Levator Veli Palatini Muscle Using Magnetic Resonance Imaging

Abstract: Background No studies have reported the circumference and diameter of the levator veli palatini muscle at multiple points along its length and from both views (frontal and lateral). The purpose of this study was to provide quantitative data regarding the levator muscle morphology along the length of the muscle using magnetic resonance imaging and advanced three-dimensional computer technology. Methods Ten Caucasian male subjects participated in the study. Subjects were scanned using a Siemens 3 T Trio. Levat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
85
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 46 publications
9
85
1
Order By: Relevance
“…The LVP of infants is approximately two-thirds of the length of the LVP of adults. 13,20,24,25 This suggests that scaling down the simulated overlap distances for surgeries on infants and children would produce the same mechanical effects on closure force. Estimated overlap amounts for adults and infants based on the overlap percentages from this study are shown in Table 2.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The LVP of infants is approximately two-thirds of the length of the LVP of adults. 13,20,24,25 This suggests that scaling down the simulated overlap distances for surgeries on infants and children would produce the same mechanical effects on closure force. Estimated overlap amounts for adults and infants based on the overlap percentages from this study are shown in Table 2.…”
Section: Discussionmentioning
confidence: 91%
“…The dimensions LVP muscle and the soft palate were determined from published measurements collected from adult magnetic resonance (MR) images (Table 1). 13,18,20,21,27,28 The curve that describes the shape of the posterior pharyngeal wall was defined based on outlines defined on midplane sagittal MR images of the soft palate Osirix software (Pixmeo, Geneva, Switzerland). 27 The initial distance between the soft palate and posterior wall was defined based on a straight-line measurement, in the relaxed position.…”
Section: Finite-element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that understanding normal anatomy is necessary in evaluating and determining dysmorphic anatomy (Perry et al, 2013). As such, there is a need for continued research regarding the anatomy and function of the velopharyngeal mechanism.…”
Section: Hard Palate Length (Hp)mentioning
confidence: 99%
“…Studies have demonstrated the use of MRI in assessing levator muscle characteristics in adults with normal velopharyngeal anatomy (Bae, Kuehn, Sutton, Conway, & Perry, 2011;Ettema et al, 2002;Perry, Kuehn, & Sutton, 2013) as well as in adults with repaired cleft palate and hypernasal speech (Ha, Kuehn, Cohen, & Alperin, 2007). Ha et al (2007) reported that participants with residual hypernasality demonstrated levator muscle dimensions that were different from levator muscle features in adults without cleft palate.…”
mentioning
confidence: 99%